2020
DOI: 10.1002/er.6022
|View full text |Cite
|
Sign up to set email alerts
|

Core@double‐shell structured multifunctional phase change microcapsules based on modified graphene oxide Pickering emulsion

Abstract: Summary New multifunctional phase change microcapsules with paraffin (Pn) as core and GO and lead tungstate (PbWO4) as double‐shell were designed by modified GO Pickering emulsion, and the effect of GO content on Pn@GO@PbWO4 microcapsules was studied. The morphology, chemical composition, and structure of Pn@GO@PbWO4 microcapsules were characterized, and their performance was studied in depth. The Pn@GO@PbWO4 microcapsules had a dense shell and a regular spherical structure. Compared with microcapsules without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In addition to SiO 2 , CaCO 3 and TiO 2 shells, the fabrication of microencapsulated PCMs with other inorganic shells has also been reported in recent years. 144–146…”
Section: Microencapsulation Of Pcmsmentioning
confidence: 99%
“…In addition to SiO 2 , CaCO 3 and TiO 2 shells, the fabrication of microencapsulated PCMs with other inorganic shells has also been reported in recent years. 144–146…”
Section: Microencapsulation Of Pcmsmentioning
confidence: 99%
“…Alternatively, it has been reported that shells of graphene oxide (GO) may be developed from the GO self‐assembly on oil/water interface within Pickering emulsions 21–23 . GO is known to be able to satisfy the demands for the shells of microcapsules, due to its special 2D material, which covers sp 2 and sp 3 ‐ hybridization carbon and considerable oxygen‐containing functional groups 24–27 . Due to the chemistry element and molecular configuration pertaining to GO, 28 GO nanosheets possess dispersibility, amphiphilicity, and flexibility in water and can adhere onto the interface in a spontaneous manner with reducing interfacial energy, which become a kind of 2D surfactant 29–32 .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] GO is known to be able to satisfy the demands for the shells of microcapsules, due to its special 2D material, which covers sp 2 and sp 3 -hybridization carbon and considerable oxygen-containing functional groups. [24][25][26][27] Due to the chemistry element and molecular configuration pertaining to GO, 28 GO nanosheets possess dispersibility, amphiphilicity, and flexibility in water and can adhere onto the interface in a spontaneous manner with reducing interfacial energy, which become a kind of 2D surfactant. [29][30][31][32] Pickering emulsion is a new type of emulsion stabilized by solid particles instead of traditional organic surfactants, usually composed of water phase, oil phase, and solid particles.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic materials with good thermal stability and TC are often combined with organic materials as a hybrid shell of MEPCMs to improve their TC. , Pickering emulsion polymerization is a novel emulsion polymerization method using solid nanoparticles instead of traditional emulsifiers, , which has the following advantages: (1) the high adhesion of Pickering particles can reduce the possibility of aggregation of emulsion droplets and enhance the stability of emulsion; (2) solid nanoparticles instead of traditional emulsifiers can avoid environmental pollution and be green; and (3) the inorganic nanoparticles with high TC as a Pickering emulsifier can improve the TC of microcapsules. ,, Therefore, the introduction of functional Pickering particles into the shell of MEPCMs via Pickering emulsion polymerization is helpful to improve TC of MEPCMs. Nano-SiO 2 , nano-TiO 2 , graphene oxide (GO), , bio-based nanoparticles, , etc. have been used as Pickering emulsifiers to prepare enhanced TC of MEPCMs.…”
Section: Introductionmentioning
confidence: 99%